2006
DOI: 10.1105/tpc.106.044065
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Lipid Peroxidation Reprograms Gene Expression and Activates Defense Markers inArabidopsisTocopherol-Deficient Mutants

Abstract: Tocopherols (vitamin E) are lipophilic antioxidants that are synthesized by all plants and are particularly abundant in seeds. Two tocopherol-deficient mutant loci in Arabidopsis thaliana were used to examine the functions of tocopherols in seedlings: vitamin e1 (vte1), which accumulates the pathway intermediate 2,3-dimethyl-5-phytyl-1,4-benzoquinone (DMPBQ); and vte2, which lacks all tocopherols and pathway intermediates. Only vte2 displayed severe seedling growth defects, which corresponded with massively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 96 publications
(160 reference statements)
8
152
2
1
Order By: Relevance
“…Previous studies have shown that the abnormal phenotype of vte2-1 seedlings is associated with massive lipid oxidation (10,11). We found that vte2-1 seedling phenotype is dependent on seed aging (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have shown that the abnormal phenotype of vte2-1 seedlings is associated with massive lipid oxidation (10,11). We found that vte2-1 seedling phenotype is dependent on seed aging (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Germinating vte2-1 seedlings accumulated high amounts of oxidized lipid and exhibited a range of aberrant developmental phenotypes, indicating an important role of tocopherols as lipid-soluble antioxidants (10,11). Despite also being tocopherol-deficient, vte1-1 seedlings did not exhibit these phenotypes, indicating that 2,3-dimethyl-6-phytyl-1,4-benzoquinol (DMPBQ), a tocopherol precursor that accumulates due to the mutation, is also able to prevent lipid peroxidation (10,11).…”
mentioning
confidence: 99%
“…Moreover, during SAR-inducing infections AZA levels increase 10,12,32 , probably due to an increase of nitric oxide/reactive oxygen species in chloroplasts 31,46 . AZI1, EARLI1 and AZI3 are upregulated by AZA and/or conditions that promote nonenzymatic lipid peroxidation 47 . Thus, the regulation and chloroplast OEM location of these HyPRPs during infection is consistent with them having roles in AZA mobilization.…”
Section: Resultsmentioning
confidence: 99%
“…The mutant vitamin e deficient2 (vte2), is defective in tocopherols biosynthesis and was shown to accumulate products of nonenzymatic lipid peroxidation (Sattler et al, 2006). The transcriptome of this mutant shows strong correlation to the flu indices and ozone ( Fig.…”
Section: Singlet Oxygen Generates a Transcriptome Footprint In Many Bmentioning
confidence: 99%